Balancing human rights and cybersecurity: Analyzing Indonesia’s legal framework - Situmeang, Ampuan; Silviani, Ninne Zahara; Prakasa, Satria Unggul Wicaksana; Tan, David; Febriyani, Emiliya (Jurnal Hukum Novelty, 2024)
Introduction to the Problem: Indonesia has been continuously developing its legal framework regarding many aspects of digital spaces, including cybersecurity, in the quest of maximizing the potentials of Industry 4.0. However, this rapid development of legal framework must be analyzed thoroughly to make sure that it’s in line with the principles of human rights. Purpose/Study Objectives: Drawing from international standards of human rights, this research focuses on analyzing the cybersecurity legal framework in Indonesia, and how the laws and regulations related to it fare against international standards of human rights. Design/Methodology/Approach: Using the normative legal research method, this research analyzes secondary data in the form of primary Indonesian and international law sources to evaluate the protection of human rights in the midst of this legal development. Findings: Findings of this research show that the legal framework in Indonesia does leave many rooms for potential human rights abuse, with normative loopholes and underestimation of potential issues regarding the denial of human rights, within digital spaces. Paper Type: Research Article